Intracranial hemorrhage in methanol toxicity: Challenging the probable heparin effect during hemodialysis - Hossein Hassanian-Moghaddam; Hooman Bahrami-Motlagh; Nasim Zamani; Seyed Amirhossein Fazeli; Behdad Behnam (Wolters Kluwer Medknow Publications, 2017)
Brain hemorrhages are rare complications of acute methanol poisoning. There is a debate on association of brain hemorrhage in methanol toxicity and application of systemic anticoagulation during hemodialysis (HD). A 70-year-old male presented to us with severe metabolic acidosis and a methanol level of 7.6 mg/dL. Ethanol and folinic acid were administered, and HD was performed. Brain computed tomography (CT) scan which was normal on presentation showed extensive bilateral subcortical supratentorial hypodensities on the 3rd day after commencing the treatment. However, the next CT scan performed 2 weeks later revealed expanding hemorrhagic transformation in previous hypodensities. Hemorrhagic changes could not be explained by patient's coagulation profile on the 3rd day. Anticoagulation agents such as heparin are used routinely during a dialysis session to prevent clot formation in dialysis circuits. This case is possibly questioning the role of heparin in hemorrhagic brain lesions of methanol intoxication.